2022
DOI: 10.1002/cssc.202201442
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Ion Intercalation Chemistry Enabling Hybrid Metal‐Ion Batteries

Abstract: To outline the role of dual‐ion intercalation chemistry to reach sustainable energy storage, the present Review aimed to compare two types of batteries: widely accepted dual‐ion batteries based on cationic and anionic co‐intercalation versus newly emerged hybrid metal‐ion batteries using the co‐intercalation of cations only. Among different charge carrier cations, the focus was on the materials able to co‐intercalate monovalent ions (such Li+ and Na+, Li+ and K+, Na+ and K+, etc.) or couples of mono‐ and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…In this sense, recently, Koleva et al concluded that co-intercalated cationic pairs enable achieving high-energy storage properties. 189 Another example is that the selective substitution of transition metal ions with electrochemically inactive ions or surface modification with oxygen-storage materials also plays a positive impact on stabilizing the anion redox reaction. 190 We can find parallels between this and the entatic state reported for iron-containing zeolites which are efficient catalysts for converting methane into methanol due to the stabilization of Fe( iv )O species by the enforced coordination geometry.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, recently, Koleva et al concluded that co-intercalated cationic pairs enable achieving high-energy storage properties. 189 Another example is that the selective substitution of transition metal ions with electrochemically inactive ions or surface modification with oxygen-storage materials also plays a positive impact on stabilizing the anion redox reaction. 190 We can find parallels between this and the entatic state reported for iron-containing zeolites which are efficient catalysts for converting methane into methanol due to the stabilization of Fe( iv )O species by the enforced coordination geometry.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure 3a, unlike PIBs and dual-ion batteries, the graphite oxide electrode with abundant oxygen-containing functional groups and defects can store both cations and anions at different active sites. [41,42] Therefore, the interaction between the cation and anion plays a crucial role in the ionic transfer at the electrode interface, especially for the HICs. To further demonstrate this conjecture, we mainly focused on investigating the solvation environment of anions and cations in different electrolytes using Fouriertransform infrared (FTIR) spectroscopy, Raman spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Solvation Structures Of Different Electrolytesmentioning
confidence: 99%
“…Hybrid lithium-sodium-ion batteries (LNBs) are a new class of batteries that combine the advantages of single lithium and sodium ones (i.e., high power and low cost) by avoiding their disadvantages (cycling stability and rate capability) [1]. The implementation of hybrid LNBs relies on the choice of electrode materials, which are able to intercalate both Li + and Na + ions [1,2]. As cathode materials, a large variety of polyanionic compounds (such as Na 3 V 2 (PO 4 ) 3 , Na 3 V 2 (PO 4 ) 2 F 3 , Na 3 V 2−x Fe x (PO 4 ) 3 , Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and layered alkali transition metal oxides (P3-Na 2/3 Ni 1/2 Mn 1/2 O 2 , P3/P2-Na 2/3 Ni 1/4 Mn 3/4 O 2 , Na 0.34 K 0.5 CoO 2 , NaKNi 2 TeO 6 , etc.) can be used due to their diversity of flexible structures, offering suitable sites for accommodation of different ions at potentials higher than 2.0 V [1,2]. In contrast to cathode materials, there are few examples of anode materials operating at potentials lower than 2.0 V [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation